Innovative ’Foray’ in Management Education - Prabhu, Narayan Krishna (Prabandhan: Indian Journal of Management, 2012)
Education in Management/B - Schools have evoked mixed response from different stakeholders. It is perceived as a ’Basket of competencies’ for effective management of different limbs of organizations. Learning too is viewed with discernment. There appears to be an unusual focus on situation oriented learning. Different approaches like experiencing, experimenting, analyzing and theorizing are being tried. The motivation level of the individual seeker is critical along with cooperative learning in groups. The seekers are often put through various innovative approaches so that they benefit. There could be real-life situations, studying the sustainability factors affecting Rural India, case writing on small and tiny entrepreneurs, writing and presenting research papers and/or studying consumer behavior dynamics by being in the market place as is evidenced in this paper. The Deans and the faculty have a challenging assignment: to confront the existing paradigms; we cannot be permitting commoditization of management programs and schools. Time has to be well spent in value additions so that all stakeholders benefit.